A Study on Women Travel Experiences Enhanced by Technology in Georgetown, Penang - Ratthinan, Senutha P. (2017)
All work and no play make not only Jack a dull boy, Jill too! Women are becoming an important entity of the travel industry as producers or consumers of the sector. Travel symbolises a form of liberation from their typical identities. The rise of new technologies has created greater opportunities for women to travel. This study will explore the motivation and travel experiences of women travellers enhanced by technology using ethnography. The findings will then underline how technologies transform the nature of tourism experiences and empower women to travel.